Contribution For Improvement Of Rice Breeding Programs Through Morphoanatomical Traits - Concenco, Germani; Brito, Giovani Greigh de; Fagundes, Paulo Roberto Reis; Scivittaro, Walkyria Bueno; Parfitt, José Maria Barbat; Melo, Thais Stradioto; Silva, Laryssa Barbosa Xavier da; Deuner, Sidnei (Journal of Agricultural Studies, 2021)
Breeding programs aim to increase grain yield and quality through selection oriented mostly by morphological and productive traits. Although morphoanatomical traits are preponderant for plant performance, they are usually time-consuming, demanding specific equipment and trained personnel. The aim of the study is to establish relationships among morphological, micromorphological and anatomical traits of rice genotypes, to support rice breeders in choosing variables to be assessed in the search for superior rice genotypes. We assessed morphological (2nd leaf and root lengths, tiller and root number), micromorphological (vein density, intervein distance, stomatal density and opening width) and anatomical (area of sclerenchyma, xylem and phloem vessels, and percentage of aerenchyma) traits. Root number and length, area of sclerenchyma and xylem and phloem vessels are proposed to be the most efficient traits to be assessed in detailed studies aiming to identify superior genotypes in rice breeding programs, from the morphophysiological point of view.